Creation, translation, and adaptation in Donald Duck Comics, by Peter Cullen Bryan - Cerqueira, Carina (2022)
To mentionDonald Duck and the imaginary world of fictional characters is,at the same time,to stress the importance of analyzing disruptive case studies. Donald Duck comics functions as a niche market, intercultural and intersemiotic. In ‘Creation, Translation,and Adaptation in Donald Duck comics’ by Peter Cullen Bryan we have the opportunity to better understand the intercultural relevance of this fictional character, the social positioning of the character and creators, and the ability to portraycultural transformations mirrored in Donald Duck.